2000
DOI: 10.2208/jscej.2000.647_67
|View full text |Cite
|
Sign up to set email alerts
|

Improving Fatigue Strength of Welded Joints by Hammer Peening and Tig-Dressing

Abstract: The effectiveness of fatigue strength improvement methods, namely TIG-dressing and hammer peening, were examined using out-of-plane gusset welded joints of high strength steel (SM570). In addition, the mechanism of each improvement method was discussed with respect to the decrease in stress concentration and residual stress at the weld toe. Finally, various methods for improving the effectiveness of these fatigue strength improvement methods are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…For new structures, the fatigue strength enhancement via HFMI treatment is usually greater than that typically achieved using TIG remelting [20], [34], particularly in high-cycle fatigue regimes. This is also expected to be the case if these two methods are used on crack-free pre-fatigued structures.…”
Section: Discussionmentioning
confidence: 99%
“…For new structures, the fatigue strength enhancement via HFMI treatment is usually greater than that typically achieved using TIG remelting [20], [34], particularly in high-cycle fatigue regimes. This is also expected to be the case if these two methods are used on crack-free pre-fatigued structures.…”
Section: Discussionmentioning
confidence: 99%
“…Weld toe grinding 1) and TIG-dressing 2) can improve weld geometry and reduce stress concentration. To reduce structural stress concentration, smoothing the stress state by drilling hole near the weld is often applied.…”
Section: Intoroductionmentioning
confidence: 99%
“…Shot peening 4), 5) and Hammer peening 2) are well-established techniques to induce residual compressive stress at weld toe. Ultrasonic Impact Treatment (UIT) can also induce residual compressive stress at weld toe 6) .…”
Section: Intoroductionmentioning
confidence: 99%
“…Fu 3) studied the grinding treatment effect on rib-to-roof weld fatigue performance of steel bridge decks and the grinding gouge sizes were proposed. Anami 4) investigated the TIGdressing and hammer peening methods using out-of-plane gusset joints and the mechanism of each improvement was discussed with respect to stress concentration and residual stress at the weld toe. Previous studies showed that grinding, hammer peening, UIT and TIG dressing are methods that can efficiently increase the fatigue life of welded joints.…”
Section: Introductionmentioning
confidence: 99%